Pengaruh TATO, CR, dan DER terhadap ROA pada PT Telekomunikasi Indonesia Tbk Tahun 2016-2024 - Ratni, Kadek Indrawati; Purnamayasa, I Komang Widya (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO), Current Ratio (CR), and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Telekomunikasi Indonesia Tbk during the period 2016-2024. The research employs a quantitative descriptive approach using quarterly data (n = 36 observations) obtained from the company’s official financial statements and the Indonesia Stock Exchange. The data were analyzed using multiple linear regression with SPSS version 27, accompanied by classical assumption tests to ensure model validity. The results show that TATO has a significant negative effect on ROA (p = 0.006; t = -2.965), indicating that increased asset efficiency does not necessarily lead to higher profitability due to high depreciation expenses and long-term digital infrastructure investments. Furthermore, CR has no significant effect on ROA (p = 0.677; t = -0.420), suggesting that liquidity is not a primary determinant of profitability in the telecommunication industry with stable cash flows. Meanwhile, DER has a significant negative effect on ROA (p = 0.045; t = -2.089), implying that excessive debt dependence reduces profit efficiency through increased interest expenses. Simultaneously, TATO, CR, and DER significantly influence ROA (F = 5.479; p = 0.004) with an R² value of 0.339, indicating that these variables explain 33.9% of profitability variation. These findings highlight the importance of capital structure management and operational cost efficiency in maintaining profitability amid digital transformation.